Remuneration committee attributes and firm performance in finance industry - Mohd. Saat, Nur Ashikin; Kallamu, Basiru Salisu (Medwell Online, 2013)
The study examines the influence of remuneration committee attributes on performance of finance companies for the period 2007-2011. Based on the data obtained from 37 finance companies listed under the finance segment of the main market of Bursa Malaysia, the result indicates significant positive relationship between RC attributes and firm performance. In terms of the coefficient of the variables, the result indicates that independent committee chair is significantly negatively related with accounting returns. This is contrary to agency theory and theoretically consistent with stewardship theory which suggests that executive directors are good stewards and in terms of conflict of the interest, the interest of the principal will prevail. This implies that the requirement for RC to be composed of only non-executive directors may not be the appropriate governance arrangement for finance companies. The result indicates a significant improvement in corporate governance in finance companies based on attributes of remuneration committee after the Malaysian Code on Corporate Governance was revised.